A 3D‐RISM/RISM study of the oseltamivir binding efficiency with the wild‐type and resistance‐associated mutant forms of the viral influenza B neuraminidase. (22nd June 2015) - Phanich, Jiraphorn; Rungrotmongkol, Thanyada; Sindhikara, Daniel; Phongphanphanee, Saree; Yoshida, Norio; Hirata, Fumio; Kungwan, Nawee; Hannongbua, Supot
Abstract: The binding affinity of oseltamivir to the influenza B neuraminidase and to its variants with three single substitutions, E119G, R152K, and D198N, is investigated by the MM/3D‐RISM method. The binding affinity or the binding free energy of ligand to receptor was found to be determined by a subtle balance of two major contributions that largely cancel out each other: the ligand‐receptor interactions and the dehydration free energy. The theoretical results of the binding affinity of the drug to the mutants reproduced the observed trend in the resistivity, measured by IC50 ; the high‐level resistance of E119G and R152K, and the low‐level resistance of D198N. For E119G and R152K, reduction of the direct drug‐target interaction, especially at the mutated residue, is the main source of high‐level oseltamivir resistance. This phenomenon, however, is not found in the D198N strain, which is located in the framework of the active‐site.